2020
DOI: 10.1177/2050313x20984120
|View full text |Cite
|
Sign up to set email alerts
|

Statin-associated anti-HMGCR immune-mediated necrotizing myopathy with dermatomyositis-like features: A case report

Abstract: Anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) immune-mediated necrotizing myopathy is a subtype of idiopathic inflammatory myopathy which may be associated with statin exposure. It presents with severe proximal muscle weakness, high creatine kinase levels and muscle fiber necrosis. Treatment with intravenous immunoglobulins and immunosuppressants is often necessary. This entity is not commonly known among dermatologists as there are usually no extramuscular manifestations. We report a rare case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…1,8,9 In addition, while rare, anti- HMGCR antibodies have been reported in other idiopathic inflammatory myopathies (IIM) and connective tissue diseases, including 1.9% of adult-onset DM cases, 6.7% of juvenile DM cases, and 1.2% of primary Sjögren's syndrome cases. 2,[9][10][11] The typical presentation of IMNM associated with anti-HMGCR antibodies is associated with a mean age of onset of 55 with a female predominance of acute to subacute onset of progressive proximal extremity weakness, more pronounced in the lower extremities. CK is elevated at least 10 times the upper limit of normal and remains elevated despite stopping statin therapy if the patient was previously exposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,8,9 In addition, while rare, anti- HMGCR antibodies have been reported in other idiopathic inflammatory myopathies (IIM) and connective tissue diseases, including 1.9% of adult-onset DM cases, 6.7% of juvenile DM cases, and 1.2% of primary Sjögren's syndrome cases. 2,[9][10][11] The typical presentation of IMNM associated with anti-HMGCR antibodies is associated with a mean age of onset of 55 with a female predominance of acute to subacute onset of progressive proximal extremity weakness, more pronounced in the lower extremities. CK is elevated at least 10 times the upper limit of normal and remains elevated despite stopping statin therapy if the patient was previously exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Gottron's papules, Gottron's sign, or heliotrope rash). 2,[4][5][6]10 This clinical entity has been recognized in the most recent 2018 ENMC dermatomyositis classification criteria as "anti-HMGCR myopathy with a DM-like rash" with a single case series comparing these patients against those with HMGCR antibodies without a DM-like rash and noting those with DM-like rashes had a younger age of onset and shorter disease duration at time of diagnosis. 13,16 In addition to the unique skin findings, the significance of the temporal relation to the patient's second COVID-19 vaccination and her prior COVID-19 infection remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGCR-IMNM patients with skin conditions usually develop pruritic erythematous papules with photosensitivity (Fig. 1E, F) [28 ▪ ,29 ▪ ,50] and sometimes show the dermatological presentations of Jessner-Kanoff disease or cutaneous lymphoma [26 ▪ ,27 ▪ ]. However, the incidence of anti-HMGCR antibody in Jessner-Kanoff disease or cutaneous lymphoma is still unknown.…”
Section: Clinical Symptoms: Focus On the Difference Between Hmgcr-imn...mentioning
confidence: 99%
“…For HMGCR-IMNM patients, the frequency of extramuscular manifestations was low. However, several studies have reported skin conditions in these patients, including Raynaud phenomenon, a nonspecific skin rash and dermatomyositis-like skin eruptions [11,15,26 ▪ –29 ▪ ,50]. HMGCR-IMNM patients with skin conditions usually develop pruritic erythematous papules with photosensitivity (Fig.…”
Section: Clinical Symptoms: Focus On the Difference Between Hmgcr-imn...mentioning
confidence: 99%